Linking alcohol-involved sexual assault to negative emotional outcomes: the relative mediating roles of shame, self-compassion, fear of self-compassion, and self-blame - Stewart, Sherry H.; Strickland, Noelle; Noguiera-Arjona, Raquel; Wekerle, Christine (Frontiers in Psychology, 2024)
Alcohol-involved sexual assault (AISA) survivors who were drinking at the time of the assault may be at risk of internalizing victim-blaming myths and stigma. Cognitive-behavioral models posit the link between AISA and negative emotional outcomes may be explained through maladaptive appraisals and coping -- i.e., characterological and behavioral self-blame, shame, low self-compassion (i.e., high self-coldness, low self-caring), and fear of self-compassion. Using a cross-sectional design and community sample of younger adults (N = 409 Canadians, M = 28.2 years old, 51.3% women), we examined these mechanisms' unique effects in mediating the associations between AISA and posttraumatic stress, general anxiety, and depressive symptoms, respectively. In terms of gender differences, AISA was more common, self-coldness higher, and general anxiety symptoms more frequent in women, and fear of self-compassion was higher in men. Using structural equation modelling that controlled for gender and the overlap between outcomes, shame emerged as the strongest mediator linking AISA with all emotional outcomes. Fear of self-compassion also partially mediated the AISA-posttraumatic stress symptom association, self-coldness partially mediated the AISA-general anxiety symptom association, and characterological self-blame fully mediated the AISA-depressive symptom association. Thus, avoidance-based processes, ruminative-/worry-based cognitions, and negative self-evaluative cognitions may be distinctly relevant for AISA-related posttraumatic stress, general anxiety, and depressive symptoms, respectively, after accounting for the overarching mediation through shame. These internalized stigma-related mechanisms may be useful to prioritize in treatment to potentially reduce AISA-related negative emotional outcomes, particularly for AISA survivors with posttraumatic stress, general anxiety, and/or depressive symptoms.